The role of angiogenic markers in adverse perinatal outcomes: fresh versus frozen embryo transfers - Woo I. (2017)
© 2017 Springer Science+Business Media, LLC Purpose: We aimed to investigate the angiogenic balance in fresh compared to frozen embryo transfers, and among neonates with adverse perinatal outcomes. Methods: This was a retrospective cohort study. All IVF cycles resulting in a singleton live birth at a university academic fertility center from January 1, 2011, to December 31, 2013, were examined. Concentrations of sFLT-1 and PlGF were measured in previously frozen serum specimens collected during early gestation at approximately 5 weeks gestation. Patients completed an electronic survey to detail perinatal outcome. Results: We identified 152 singleton live births (103 fresh, 49 frozen). Demographic characteristics were similar between the two groups. Ratios of sFlt-1:PlGF were not different between fresh and frozen transfers. Neonates from fresh cycles had a mean birth weight 202 g lighter (p = 0.01) than frozen cycles, after adjusting for gestational age. Among babies born with poor perinatal outcomes, there was a difference in sFlt-1:PlGF ratios after adjusting for race. In non-Asians, infants born small for gestational age (SGA) ( < 10th percentile) had significantly higher sFLT-1:PLGF ratio, median ratio (0.21 vs 0.12, p = 0.016). Conclusions: Fresh transfers were associated with lower birth weight infants compared to frozen transfers. While there was no difference in sFlt-1:PlGF ratios between fresh and frozen transfers, these ratios were significantly lower in SGA infants, suggesting an imbalance in angiogenic markers during placentation.